Attitudes of faculty members towards the use of children aged (5-12 years) for social media. (Damascus University Journal of educational and Psychologyical sciences, 2021)
The research aimed to measure the attitudes of faculty members towards the use of children (5-12 years) for social media.The researcher used the descriptive analytical method, and the research was conducted on a sample of faculty members, who numbered (219) faculty members in four colleges from the University of Damascus, at a rate (42.6%) of the size of the original community. The study tools were represented by a scale of trends that included four dimensions (social, political, educational, and entertainment).  Search results showed:- The attitudes of faculty members towards the use of children (5-12 years) for social media sites were negative and they did not prefer the use of children of this age group for social media sites that affect negative effects while their attitudes according to the educational, and entertainment dimensions were neutral.-There were significant differences between the attitudes of faculty members in theoretical and applied colleges towards children's use of social media sites in the educational dimension in favor of the attitudes of faculty members in applied colleges-There was no statistically significant difference between the averages of the grades of faculty members' attitudes towards the use of children of the age group (5-12) years for social media sites, depending on the variable of the academic grade.
Keywords: attitudes; social media; faculty members